2009
DOI: 10.1002/jnr.22071
|View full text |Cite
|
Sign up to set email alerts
|

Asiatic acid, a pentacyclic triterpene from Centella asiatica, is neuroprotective in a mouse model of focal cerebral ischemia

Abstract: Asiatic acid, a triterpenoid derivative from Centella asiatica, has shown biological effects such as antioxidant, antiinflammatory, and protection against glutamate-or β-amyloid-induced neurotoxicity. We investigated the neuroprotective effect of asiatic acid in a mouse model of permanent cerebral ischemia. Various doses of asiatic acid (30, 75, or 165 mg/kg) were administered orally at 1 hr pre-and 3, 10, and 20 hr postischemia, and infarct volume and behavioral deficits were evaluated at day 1 or 7 postische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
90
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(95 citation statements)
references
References 38 publications
4
90
0
1
Order By: Relevance
“…In our experiments, AA attenuated the decline of the MMP induced by Glu. Our data corroborate the results of a previous study, which reported that AA prevents the collapse of the MMP in rotenone-induced neuronal damage [14] and in the oxygenglucose deprivation (OGD) cell culture model of ischemia [17] .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our experiments, AA attenuated the decline of the MMP induced by Glu. Our data corroborate the results of a previous study, which reported that AA prevents the collapse of the MMP in rotenone-induced neuronal damage [14] and in the oxygenglucose deprivation (OGD) cell culture model of ischemia [17] .…”
Section: Discussionsupporting
confidence: 92%
“…The animals were divided into four experimental groups: control, MSG, MSG+50 mg/kg AA and MSG+100 mg/kg AA. The AA doses used in this study were chosen on the basis of previously published experiments [17] . AA was administered after MSG treatment on PD 14 and daily thereafter for 30 d. The mice then performed the Morris water maze.…”
Section: Drug Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that Asiatic acid has a variety of pharmacological effects on anti-inflammation, 8,9) anti-tumor, 10) neuroprotection. 11) In particular, Asiatic acid has been shown to be a hepatoprotective agent. A number of studies demonstrated that Asiatic acid can protect liver from injury via mechanisms underlying antimitochondrial stress and cellular antioxidant system in cultured hepatocytes and Kupffer cells, and in a mouse model induced by D-galactosamine and lipopolysaccharides.…”
mentioning
confidence: 99%
“…Some reports stated that AA is a promising agent in the treatment of stroke. AA exerts neuroprotection by maintaining the stability of the blood brain barrier and by protecting the mitochondrial functions (10,12,13,20).…”
mentioning
confidence: 99%